1992
DOI: 10.3759/tropics.1.233
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Ecosystem Studies on Mangrove Forests-Charcoal Industry and Primary Productivity of Secondary Stands.

Abstract: Abstract. In Ranong province, southern Thailand, the biomass and net primary production of secondary mangrove forest stands were estimated and compared with the amount of mangrove wood used for the charcoal industry. Using the naturally regenerated mangrove stands, the net primary production was calculated by the allometric equation and the summation method. The wood amount used for the charcoal factory in Ranong province was calculated from the kiln volume, the burning frequency, and the wood packing capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The stems of Rhizophoraceae tended to show high SG compared to those of the other species, such as X. granatum (Clough & Scott 1989). Komiyama et al . (1992) estimated the SG of R. apiculata at 0.769.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stems of Rhizophoraceae tended to show high SG compared to those of the other species, such as X. granatum (Clough & Scott 1989). Komiyama et al . (1992) estimated the SG of R. apiculata at 0.769.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the intraspecific difference in specific gravity was small because the close relationships within each species (Clough & Scott 1989). Komiyama et al (1992) estimated the SG of R. apiculata at 0.769. Furuno (1977,1979) estimated the specific gravity of wood of Bruguiera and Sonneratia species at 0.800 and 0.450, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A comparison of the MF14 and PMF with the other mangrove sites found that the BGB of MF14 and PMF (74.76 and 37.61 t ha -1 , respectively) was lower than a primary mangrove forest in Halmahera, Indonesia (110.8-180.7 t ha -1 ) (Komiyama et al 1988). However, in the present study, the BGB of MF14 was similar to that reported by Komiyama et al (2000) in the Satun Province, southern Thailand who found that the belowground biomass of a secondary mangrove forest dominated by C. tagal was around 87.50 t ha -1 .…”
Section: Vegetation Biomassmentioning
confidence: 92%
“…Therefore, we used the common allometric equation by Komiyama et al (2005) to estimate aboveground biomass for all species except for Rhizophora species because the equation excludes stilt root biomass. For the Rhizophora species, we used an allometric equation by Komiyama et al (1988), which can be used to calculate each part.…”
Section: Methodsmentioning
confidence: 99%
“…However, since the R. stylosa community at PR has densely developed stilt roots (Figure 4), the allometric equation of Komiyama et al (1988) cannot be applied to estimate the stilt root biomass. Therefore, the diameter and length of all stilt roots in several 5 meters square quadrats and the wood density were measured (Nishino et al, 2015).…”
Section: Methodsmentioning
confidence: 99%